2021
DOI: 10.1002/mnfr.202000977
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review Assessing Clinical Utility of Curcumin with a Focus on Cancer Prevention

Abstract: Scope: There is extensive pre-clinical evidence for utility of curcuminoids across many diseases with a particular focus on cancer prevention, yet there remains a paucity of clinical evidence for its approved use. To assess current knowledge on the broader potential for clinical efficacy of curcumin and in particular, in cancer prevention strategies, this study undertook a systematic review determining the number and quality of randomized controlled trials (RCTs) undertaken across any pathology. Methods and Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Curcumin and anthocyanin extracts have been demonstrated to be phytochemicals with potential antitumor activity in CRC [8,9,[16][17][18][19]. A recent systematic review shows a significant number of clinical trials conducted with curcumin formulations in a cancerpreventive setting with positive outcomes, but only 30% include putative biomarkers of efficacy as clinical endpoints [9]. Conversely, data relating to the CRC-preventive activity of anthocyanins are mainly based on observational studies [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Curcumin and anthocyanin extracts have been demonstrated to be phytochemicals with potential antitumor activity in CRC [8,9,[16][17][18][19]. A recent systematic review shows a significant number of clinical trials conducted with curcumin formulations in a cancerpreventive setting with positive outcomes, but only 30% include putative biomarkers of efficacy as clinical endpoints [9]. Conversely, data relating to the CRC-preventive activity of anthocyanins are mainly based on observational studies [19].…”
Section: Discussionmentioning
confidence: 99%
“…This natural polyphenol shows antioxidant and anti-inflammatory effects through the regulation of numerous intracellular targets that control CRC cell growth in in vitro and in vivo studies [8]. On the other hand, clinical studies in humans are very few and have shown conflicting results [8,9]. A wide range of curcumin formulations have been explored during recent years in order to improve its curcumin poor bioavailability and low oral absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin has a proven ability to counter chemoresistance in cancer cells (14,19,20). The ability of curcumin to modulate the regulatory networks governing the balance of cell survival and induction of cell death is well established (20,21). Curcumin has been demonstrated to amend the expression of molecules central to chemoresistance including members of the ABC drug efflux transporter family (14,17,22).…”
Section: Introductionmentioning
confidence: 99%
“…In renal tubular epithelial cells, curcumin was also shown to obviate high glucose-induced epithelial-to-mesenchymal transition (EMT) (23). High glucose conditions can aggravate the invasion and migration (24), while curcumin can impede the metastatic events in a variety of malignancies (18,21). Antineoplastic potential, metabolic modulatory ability, and chemosensitizing property along with safety investigations (15,16,20,21,25,26) provide an edge to curcumin over other phytochemicals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation